A comprehensive consideration of friction effect on small-to-large strain stiffness: floating versus fixed-ring oedometer cells - Younggeun Yoo; Jong-Sub Lee; WooJin Han; Junghee Park (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract We investigate the deformation and shear wave velocity in floating- and fixed-ring cells when the specimen diameter-to-height ratio is 1.0 and 1.3. In this study, floating- and fixed-ring oedometer cells are combined with bender elements for measuring the shear wave velocity, and specimens are prepared at four different relative densities Dr = 30%, 50%, 70%, and 90%. All specimens experience static step loading when the vertical effective stress changes from 0 to 500 kPa. The load-deformation curves obtained under different boundary conditions show that the soil fabric tends to be denser more readily in the floating-ring cells than in the fixed-ring cells. Similarly, the geometry of the specimen plays an important role in the load-deformation response of soils. More significant deformation occurs during the loading history as the specimen diameter-to-height ratio increases. Clearly, the combination of a floating-ring cells with a larger ratio minimizes the boundary effect on the engineering soil properties; otherwise, underestimation prevails. Assuming the friction angle at the soil-wall interface, force equilibrium analyses for the thickness of soil dz in the oedometer cell allow us to anticipate the effective stress distribution along the specimen depth z. Results and analyses conducted in this study highlight that the design parameters obtained in the laboratory study should be selected carefully; otherwise, we may underestimate critical soil properties that can be used in a wide range of engineering projects. This study proposes an innovative laboratory experimental design to minimize the effects of friction on soil properties.